2008
DOI: 10.1002/hyp.7152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of global optimization algorithms for parameter calibration of a computationally intensive hydrologic model

Abstract: Abstract:With the popularity of complex hydrologic models, the time taken to run these models is increasing substantially. Comparing and evaluating the efficacy of different optimization algorithms for calibrating computationally intensive hydrologic models is becoming a nontrivial issue. In this study, five global optimization algorithms (genetic algorithms, shuffled complex evolution, particle swarm optimization, differential evolution, and artificial immune system) were tested for automatic parameter calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 54 publications
3
97
0
1
Order By: Relevance
“…GAs have been used to minimize errors in searching optimized model parameters based on inversion model [Reed et al, 2000;Mohanty, 2008, 2009;Zhang et al, 2009;Shin et al, 2012;. Zhang et al [2008] integrated several global optimization algorithms (i.e., GA, SCE-UA, PSO, etc.) with Soil and Water Assessment Tool and compared their performances in calibrating model input parameters.…”
mentioning
confidence: 99%
“…GAs have been used to minimize errors in searching optimized model parameters based on inversion model [Reed et al, 2000;Mohanty, 2008, 2009;Zhang et al, 2009;Shin et al, 2012;. Zhang et al [2008] integrated several global optimization algorithms (i.e., GA, SCE-UA, PSO, etc.) with Soil and Water Assessment Tool and compared their performances in calibrating model input parameters.…”
mentioning
confidence: 99%
“…Zhang et al (2009) found GA to perform well compared to other optimization algorithms in the calibration of the SWAT model. Multi-objective GA have been used in the calibration of this model (Bekele and Nicklow, 2007;Whittaker et al, 2007) as well.…”
Section: Optimization Methodologymentioning
confidence: 96%
“…The validation has both low P-factor and low R-factor, though its NSE and r 2 are high, which means the uncertainty exists in the result of the validation and the outcomes of the uncertainty and the accuracy are not consistent. The longer the period is, the more the inconsistency of the hydrological process increases, which makes calibration and validation more difficult [54].…”
Section: Source Of Errormentioning
confidence: 99%